The impact of ringgit de-pegging on the Malaysian capital market - Ahmad, Nor Hayati; Taufil Mohd, Kamarun Nisham; Abu Bakar, Ab Malek Foad; Isa, Mohamad Yazid (Universiti Utara Malaysia, 2007)
The sudden announcement on July 21 2005 by the Central Bank of Malaysia to dismantle the pegging of Malaysian ringgit against US Dollar caused a stir in the Malaysian financial market.This announcement was unexpected as Malaysia has implemented de-pegging almost seven years since September 1998.This policy change motivates us to measure statistically the announcement impact of de-pegging of Ringgit, to investigate its effects on the various sectors of the economy and accordingly, to identify the sectors most significantly affected by the change from the Ringgit fixed rate to floating rate system.Further investigation is conducted to compare between the Malaysian market’s reaction to the announcement and other international stock markets such as the stock markets of its trading partners. Selected Malaysian economic variables such as interest rate and exchange rate are tested to determine its relationship with the market return.Statistical tools such as descriptive statistic, Single Index Market Model, correlation and cointegration technique are used in the analysis.Our findings indicate that the investors and overall market responded favorably to the move by the Malaysian government to untie the pegging of RM3.80 to USD1.The announcement resulted in positive raw return and a positive abnormal return of 1.93% and 2.31% respectively. Our result also indicate that the sector that is most effected by the de-pegging is the finance sector which recorded positive raw and adjusted returns of 2.12% and 0.56% respectively.In contrast plantation sector recorded negative raw and adjusted return of -0.5% and -2.05% respectively.We note that Malaysian stock market is less vulnerable to movement of other stock markets such as S&P 500, Singapore, Hong Kong, Jakarta, Philippine and Bangkok during the pegging period. However, Malaysian interest rate is negatively correlated with six out of nine countries with the correlation to US interest rate being the lowest at -0.6481.In contrast it is positively correlated with its trading partners after de-pegging.Overall we find that the continuing support of the investors reflect that it is a good policy decision for Malaysia to move from fixed exchange rate regime to a managed floating rate regime where the Ringgit can find its true value.